AKAL DAN AGAMA PEREMPUAN (Perspektif Hadis Nabi dan Psikologi) - Ansori, Ibnu Hajar (UNIVERSUM, 2018)
This article is reinterpretation of hadith meaning with integration-interconnection paradigm, focusing on hadith study on thought and religion of women through psychology approach. In the hadith, the Prophet stated that almost people in hell are women; less their thought (na>qis}a>t ‘aql), and also less their religion (na>qis}a>t di>n). Contextually, this speech has gender discrimination. It consists of a meaning that women are not as smart as men, and their religion as well. it Therefore, feminists mention that there is misogyny inside. However, if is studied contextually, based on investigating the asba>b al-wuru>d, women thought psychology study, and their life reality study, it can be concluded that there is no misogyny factor inside. In contrast, there is knowledge direction that is needed to be investigated inside the speech. The findings of this study show that the change of women’s thought is related to some functions of thought that is different with men’s thought including the different of hormonal changes and its adaptation with menstruation cycles that influence some parts of thought function and decrease their roles in spiritual activities Key words: thought, religious, women, psycho-social, hadith